2020
DOI: 10.1111/jocn.15139
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing self‐management behaviours among patients with type 2 diabetes mellitus in the Solomon Islands

Abstract: Aims and objectives This study aims to explore the current state of self‐management behaviours among persons with type 2 diabetes mellitus in the Solomon Islands and to discuss the factors influencing these behaviours. Background The prevalence of diabetes and diabetes complications is increasing in the Solomon Islands. However, the effective diabetes prevention and care are not provided in the country. Design This is a cross‐sectional study. Methods A convenience sample of 150 persons with type 2 diabetes mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
2
12
0
1
Order By: Relevance
“… 69 This assertion is supported by studies on T2DM self‐management and glycemic control among individuals with T2DM in China that less than 40% of Chinese patients with T2DM have achieved the target goal, and only 9.2%–16.7% of them perform self‐management behaviors adequately. 70 , 71 The results of the present study demonstrated good self‐management on T2DM similar to the findings in Solomons Island 72 and the USA. 73 There was, however contrary finding of similar studies globally.…”
Section: Discussionsupporting
confidence: 87%
“… 69 This assertion is supported by studies on T2DM self‐management and glycemic control among individuals with T2DM in China that less than 40% of Chinese patients with T2DM have achieved the target goal, and only 9.2%–16.7% of them perform self‐management behaviors adequately. 70 , 71 The results of the present study demonstrated good self‐management on T2DM similar to the findings in Solomons Island 72 and the USA. 73 There was, however contrary finding of similar studies globally.…”
Section: Discussionsupporting
confidence: 87%
“…Bezo et al. (2020) found that the cultural beliefs and practices caused a discrepancy between the various dimensions of illness perception. A study of patients with type 2 diabetes in Solomon Island revealed low scores for the following dimensions of illness perception: control, treatment and coherence (Bezo et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…(2020) found that the cultural beliefs and practices caused a discrepancy between the various dimensions of illness perception. A study of patients with type 2 diabetes in Solomon Island revealed low scores for the following dimensions of illness perception: control, treatment and coherence (Bezo et al., 2020). The above findings emphasise that illness perception is shaped by the social and cultural contexts (Bezo et al., 2020; Sawyer et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this interactive, dynamic, and daily process, the individual, along with one's family, society, and healthcare workers, uses his/her capacity to alter lifestyle, control symptoms and cure oneself [10]. Diabetes self-management is influenced by various factors such as HbA1c, occupation, smoking, knowledge of and one's perception of diabetes, self-efficacy, social support, education, family income, age, ethnicity, BMI, diabetes duration, sex, place of residence, marital status, and kind of treatment [11][12][13][14][15][16][17][18][19][20][21][22]. Various studies have investigated the extent of self-management behaviour such as use of medicine, insulin, and urine and blood test among diabetics, concluding that adherence to these guidelines is low among diabetics.…”
Section: Introductionmentioning
confidence: 99%